2021
DOI: 10.1021/acs.iecr.0c04963
|View full text |Cite
|
Sign up to set email alerts
|

Cellobiose as a Model Carbohydrate for Predicting Solubilities in Nonaqueous Solvents

Abstract: The use of nonaqueous solvents for conversion of biomass molecules into platform chemicals and fuels is hindered by a lack of solubility data and models. Accordingly, the solubility of the model carbohydrate, cellobiose, was measured at 20 °C in 18 organic liquids and water. Solubility ranged from <0.001 g L–1 in hydrocarbon solvents to >100 g L–1 in hydrogen bond acceptor solvents. Three models were analyzed to evaluate accuracy and to understand factors that affect cellobiose solubility: Hansen’s solubility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…184 Thus, water-oil biphasic systems can increase the strength of hydrogen bonds between molecules and water molecules by forming hydrogen-rich local solvent regions around the OH groups of the reactants, thereby influencing the solubility of the substance and further accelerating the reaction rate. 185,186 Esteban et al 54 reported the selective HDO of sugars from lignocellulose to produce 5-HMF and furfural in a water/MIBK biphasic system, as shown in Fig. 18a.…”
Section: Reactant Solubilitymentioning
confidence: 99%
“…184 Thus, water-oil biphasic systems can increase the strength of hydrogen bonds between molecules and water molecules by forming hydrogen-rich local solvent regions around the OH groups of the reactants, thereby influencing the solubility of the substance and further accelerating the reaction rate. 185,186 Esteban et al 54 reported the selective HDO of sugars from lignocellulose to produce 5-HMF and furfural in a water/MIBK biphasic system, as shown in Fig. 18a.…”
Section: Reactant Solubilitymentioning
confidence: 99%
“…The mass of cellobiose recovered in aqueous acid solution is denoted as 𝑚 cellobiose and the mass of solvent in the test solution is given as 𝑚 solv . As the maximum solubility limits of cellobiose were unknown and could vary widely among solvents [90], the dissolution of cellobiose was studied below the saturation point for individual solvents.…”
Section: Cellobiose Solubility Measurementmentioning
confidence: 99%
“…Recently, gamma-valerolactone has been highlighted as a biomass-derived organic solvent that has high dissolution of lignin but low dissolution rate of carbohydrates; , its use in GVL/water and GVL/water/acids has been widely applied for the delignification of lignocellulosic biomass with enhanced performances. Given the advantages of both alkaline/water and GVL/water for lignocellulosic biomass pretreatment, we hypothesized that the combination of alkaline and GVL can adopt advantages from both sides, leading to a technique that not only improves delignification but also suppresses the loss of carbohydrates. However, trials on the combined GVL/alkaline pretreatment have not been carried out, and the effect of GVL on alkaline delignification remains unknown.…”
Section: Introductionmentioning
confidence: 99%